Pengaruh Kolaborasi Strategi dan Information Sharing terhadap Logistics Performance yang dimediasi Logistics Capability Pada PT. Myglobal Logistik Internasional - Qatrun Nada Mutiah Gusfi; Nofrisel Nofrisel; Dinar Dewi Kania (AKUNTANSI 45, 2024)
In the broader logistics industry, there are several trends and challenges that might impact the performance of PT. MyGlobal Logistik Internasional. In an increasingly complex era of globalization, logistics companies face significant challenges in maintaining competitive performance. This study aims to determine the direct and indirect effects of strategic collaboration and Information sharing on logistics performance, mediated by Logistics capability at PT. MyGlobal Logistik Internasional. The method used in this research is a descriptive quantitative method with a survey approach. The population includes all service users at PT. MyGlobal Logistik Internasional, consisting of leaders, supervisors, and operational staff. The sampling technique employed is purposive sampling with a total of 90 respondents. Data collection was carried out using a questionnaire that had been tested for reliability and validity. This study uses path analysis SEM with the Smart Partial Least Square (PLS) software version 3.2.9. The research results show that strategic collaboration has a positive and significant impact on Logistics capability. Information sharing has a positive and significant impact on Logistics capability. Strategic collaboration has a positive and significant impact on logistics performance. Information sharing has a positive and significant impact on logistics performance. Logistics capability at PT. MyGlobal Logistik Internasional has a positive and significant impact on logistics performance.